Performing gender: The construction of Black males in the hip-hop industry - Sasaki-Picou, Nayo (Contingent Horizons: The York University Student Journal of Anthropology, 2019)
In 2011, a hip-hop artist by the name of Frank Ocean challenged the world of hip-hop in North America, announcing news about his sexual orientation. Many people have suggested that his announcement has created a new outlet for black male hip-hop artists to be able to express themselves beyond heteronormative behaviour. However, there exists a historically informed cultural norm of black male behaviour that continues to be deeply ingrained in American society. This paper will examine the hip-hop industry in North America and suggest that Ocean’s announcement did not have any transformative effect in the hip-hop industry.